2017
DOI: 10.3928/00989134-20160901-01
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an Interdisciplinary Transitional Care Quality Improvement Project on Self-Management and Health Care Use in Patients With Heart Failure

Abstract: Heart failure (HF) accounts for most U.S. Medicare hospital admissions. The purpose of the current study was to evaluate the effectiveness of a care transitions quality improvement (QI) intervention on self-management and readmission rates in older adults with HF. A quasi-experimental, descriptive study was conducted with 66 patients with HF in three medical units in a 489-bed Midwestern acute care hospital. The intervention included a nurse coach visit and follow up, pharmacy medication education and reconcil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Patients indicated challenges in learning self-management skills and applying self-management at home. Several clinical trials have recommended self-management strategies during transitions (Aboumatar et al, 2019; Hoover et al, 2017). These studies demonstrated the importance of self-management education before discharge, a nurse-coach visit, and follow-up self-management training.…”
Section: Discussionmentioning
confidence: 99%
“…Patients indicated challenges in learning self-management skills and applying self-management at home. Several clinical trials have recommended self-management strategies during transitions (Aboumatar et al, 2019; Hoover et al, 2017). These studies demonstrated the importance of self-management education before discharge, a nurse-coach visit, and follow-up self-management training.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some articles showed about the guidance regarding pharmacological treatment, 16,[25][26][27][39][40][41][42][43] of which most pointed out the importance of the participation of the pharmacist in counseling people with HF and their families. [25][26]39,[41][42][43][44] It is believed that some problems resulting from low understanding of pharmacological treatment are solved by offering written instructions, with easy to understand language, emphasizing the name of the medications, dose, route and time of administration, indications and possible adverse reactions.…”
Section: Pharmacological and Non-pharmacological Treatmentmentioning
confidence: 99%
“…However, there was no consensus about the most appropriate time frame for this consultation. 19,23,26,28,40,44,[49][50][51][52] Although there is no consensus about the deadline for the post-discharge consultation of people with HF, it is suggested that it should be performed between seven and 14 days after discharge, not exceeding 30 days. 26,40,[49][50][51] In addition, to contribute to improvements in post-discharge follow-up, appointments can be scheduled near the residence of the person with HF and provide ways for them or their relatives to be reminded about the day and time of the scheduled consultation.…”
Section: Activities Of Daily Living and Existing Resourcesmentioning
confidence: 99%
See 2 more Smart Citations